2000
DOI: 10.1002/1529-0131(200011)43:11<2513::aid-anr19>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule 1 underlies the functional heterogeneity of synovial cells in patients with rheumatoid arthritis: Involvement of cell cycle machinery

Abstract: Objective. To investigate whether synovial cells from rheumatoid arthritis (RA) synovium can be divided into 2 functionally different subpopulations: active or proliferative cells and apoptotic cells. Methods. Expression of cell surface and cyto-plasmic molecules on synovial cells was assessed by immunohistochemistry, flow cytometry, or Western blotting. Cells were categorized as intercellular adhesion molecule 1 (ICAM-1) positive or negative based on positive and negative selection of antibody-coated beads. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Accumulating evidence from in vitro and in vivo studies suggests that p53-dependent pathway plays an adaptive role in FLS by keeping them in the quiescent state. For example, synovial lining cells and cultured RA FLS that are in the G0/G1 state show characteristic up-regulated expression of p53) [5,6] (see also Discussion).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Accumulating evidence from in vitro and in vivo studies suggests that p53-dependent pathway plays an adaptive role in FLS by keeping them in the quiescent state. For example, synovial lining cells and cultured RA FLS that are in the G0/G1 state show characteristic up-regulated expression of p53) [5,6] (see also Discussion).…”
Section: Introductionmentioning
confidence: 92%
“…The expression of p27 mRNA is constant throughout the cell cycle, and p27 availability is regulated mostly at the protein level by translational control and ubiquitin-mediated proteolysis [16]. Interestingly, p21 and p27 seem to participate in the maintenance of RA FLS in quiescent G0/G1 state both in synovial tissue and in culture conditions [5,6]. Opposite to CDKIs, proliferating cell nuclear antigen (PCNA) and survivin are positive regulators of the cell cycle progression and the expression of these proteins is highly elevated in proliferating cells [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Discrepancies in these studies might be the result of differences in the stage of synovial tissue used for isolation of synoviocytes, the type of synoviocytes, or culture conditions. 11,12 Defective apoptosis is a second mechanism contributing to synovial hyperplasia. Whereas initial studies indicated increased levels of apoptosis in the rheumatoid synovium, recent investigations have demonstrated both in vivo and in vitro evidence of the resistance of synoviocytes to apoptosis.…”
Section: Proliferation Versus Apoptosismentioning
confidence: 99%
“…We previously reported that ICAM‐1–positive RA synovial cells, which also express Fas, undergo growth arrest and subsequent apoptosis, whereas ICAM‐1–negative cells are proliferative (8). However, little is known about the mechanism of induction of these apoptotic synovial cells.…”
mentioning
confidence: 99%